University Students Perceiving the Complexity of Legal Lexicological Derivations: A Linguistic and Pedagogical Analysis - Nguyen, Ai Nhan; Vu, Tuan Van; Le, Thuy Thanh (International Journal of Language Education, 2025)
Legal language is characterized by its specialized lexicology, often formed through derivational processes such as affixation, nominalization, and semantic derivation, making legal texts more challenging to understand. This research examined how university students majoring in legal English linguistics recognize, interpret, and manage the complicated nature of legal vocabulary derivations while acquiring legal English. The study employed a mixed-methods approach, using a researched-made questionnaire with forty Likert scale items and semi-structured interviews to examine students' viewpoints regarding the derivational complexity of legal vocabulary. It emphasized critical areas of student challenges, such as differentiating between plain and legal meanings, comprehending nominalized phrases, and managing the cognitive strain associated with these derived concepts. Besides, the study also explored students' strategies to overcome these challenges, such as breaking down words into their root forms, using context clues, and referencing dictionaries. The results highlighted significant gaps in students' ability to fully grasp the nuances of legal derivations, suggesting the need for more targeted pedagogical strategies in legal English instruction. The study concluded with recommendations for improving vocabulary teaching to enhance learners’ comprehension, retention, and application of legal terms, focusing on addressing the derivational complexities that hinder students' understanding of legal texts. The findings would be resourceful greatly to those who are involved in the linguistics field, especially in legal English teaching and learning in an English as a foreign language country.